Sedimentology and chronology of unconsolidated alluvial fans of the Quadrilátero Ferrífero (Central Brazil): implications for landscape dynamics in the Late Quaternary - Lopes, Fabrício Antonio; Castro, Paulo de Tarso Amorim; Carvalho, Alex de; Lana, Cláudio Eduardo (Revista Brasileira de Geomorfologia, 2025)
This paper identifies and discusses the paleoenvironmental characteristics of the Quadrilátero Ferrífero based on studies of unconsolidated alluvial fans and the chronological organization of their respective sedimentary facies. These alluvial fans were submitted to stratigraphic survey and dating by Optically Stimulated Luminescence (OSL) and, subsequently, their ages and faciological characteristics were compared with the paleoclimatic and paleotectonic data available for the region. The description and interpretation of the sedimentary facies evidenced a lack of aggradational processes, which are inactive. About 40% of the identified facies are plastic (Gmm) and pseudoplastic (Gcm) debris flows interspersed with occasional channel-filling facies (Gt), hyper- concentrated (Sm), and mud (Fm) flows. The unconsolidated alluvial fans of the Quadrilátero Ferrífero had their genesis throughout the Pleistocene, mainly in a dry climate, with vegetation retraction and sedimentary filling of river valleys. Climatic oscillations to establish a humid environment increased the flow of drainage courses and, consequently, erosion of the deposits. However, it was cenozoic tectonics that acted most strongly in the dismantling of the fans through strong fluvial incision in the Holocene, caused by uplifts of the Brazilian continental shelf.